2008
DOI: 10.1111/j.1364-3703.2007.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Bursaphelenchus xylophilus: opportunities in comparative genomics and molecular host–parasite interactions

Abstract: SUMMARY Most Bursaphelenchus species are fungal feeding nematodes that colonize dead or dying trees. However, Bursaphelenchus xylophilus, the pine wood nematode, is also a pathogen of trees and is the causal agent of pine wilt disease. B. xylophilus is native to North America and here it causes little damage to trees. Where it is introduced to new regions it causes huge damage. The most severely affected areas are found in the Far East but more recently B. xylophilus has been introduced into Portugal and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
116
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 68 publications
0
116
0
Order By: Relevance
“…RNAi has been used to investigate gene function in B. xylophilus (Wang et al, 2007;Park et al, 2008). RNAi offers the possibility to analyze gene function in vitro on a routine basis; although the molecular biology of the interactions between B. xylophilus and its host at a molecular level and the molecular basis of the pathogenicity of the nematode are still poorly understood (Jones et al, 2008). Park et al (2008) compared three methods of transferring dsRNA into B. xylophilus and found that microinjection was the most efficient, compared to soaking and electroporation.…”
Section: Discussionmentioning
confidence: 99%
“…RNAi has been used to investigate gene function in B. xylophilus (Wang et al, 2007;Park et al, 2008). RNAi offers the possibility to analyze gene function in vitro on a routine basis; although the molecular biology of the interactions between B. xylophilus and its host at a molecular level and the molecular basis of the pathogenicity of the nematode are still poorly understood (Jones et al, 2008). Park et al (2008) compared three methods of transferring dsRNA into B. xylophilus and found that microinjection was the most efficient, compared to soaking and electroporation.…”
Section: Discussionmentioning
confidence: 99%
“…Any uncut wilted tree and untreated dead wood can be a reservoir of nematodes, as well as insects, for the following year as insect vectors will emerge carrying large numbers of nematodes (Schrader & Unger, 2003;Jones et al, 2008). The complex ecology of B. xylophilus …”
Section: Discussionmentioning
confidence: 99%
“…Serious PWD symptoms are associated with higher temperatures, occurring only where average summer temperatures exceed 20ºC (Jones et al, 2008). In Madeira Island, after the first detection of PWN, an intensive survey has been conducted to evaluate the distribution of the nematode throughout the island and the PWN was detected in 22.8 % of the analysed 500 P. pinaster wood samples.…”
mentioning
confidence: 99%
“…However, native American conifers are tolerant or resistant to B. xylophilus, and consequently this nematode has caused little damage (Mamiya, 1983;Jones et al, 2008). At the beginning of the 20th century, the PWN was introduced in Japan and became responsible for massive mortality of native pine trees (Pinus densiflora, P. thunbergii and P. luchuensis).…”
Section: Introductionmentioning
confidence: 99%